A Computer Simulation of Community Pharmacy Practice for Educational Use - Bindoff, I.; Ling, T.; Bereznicki, L.; Westbury, J.; Stafford, Leanne; Peterson, G.; Ollington, R. (American Association of Colleges of Pharmacy, 2014)
OBJECTIVE: To provide a computer-based learning method for pharmacy practice that is as effective as paper-based scenarios, but more engaging and less labor-intensive.DESIGN: We developed a flexible and customizable computer simulation of community pharmacy. Using it, the students would be able to work through scenarios which encapsulate the entirety of a patient presentation. We compared the traditional paper-based teaching method to our computer-based approach using equivalent scenarios. The paper-based group had 2 tutors while the computer group had none. Both groups were given a prescenario and postscenario clinical knowledge quiz and survey.ASSESSMENT: Students in the computer-based group had generally greater improvements in their clinical knowledge score, and third-year students using the computer-based method also showed more improvements in history taking and counseling competencies. Third-year students also found the simulation fun and engaging.CONCLUSION: Our simulation of community pharmacy provided an educational experience as effective as the paper-based alternative, despite the lack of a human tutor.